Bifidobacterium dentium-derived y-glutamylcysteine suppresses ER-mediated goblet cell stress and reduces TNBS-driven colonic inflammation. (1st January 2021) - Engevik, Melinda A.; Herrmann, Beatrice; Ruan, Wenly; Engevik, Amy C.; Engevik, Kristen A.; Ihekweazu, Faith; Shi, Zhongcheng; Luck, Berkley; Chang-Graham, Alexandra L.; Esparza, Magdalena; Venable, Susan; Horvath, Thomas D.; et al.
ABSTRACT: Endoplasmic reticulum (ER) stress compromises the secretion of MUC2 from goblet cells and has been linked with inflammatory bowel disease (IBD). Although Bifidobacterium can beneficially modulate mucin production, little work has been done investigating the effects of Bifidobacterium on goblet cell ER stress. We hypothesized that secreted factors from Bifidobacterium dentium downregulate ER stress genes and modulates the unfolded protein response (UPR) to promote MUC2 secretion. We identified by mass spectrometry that B. dentium secretes the antioxidant γ-glutamylcysteine, which we speculate dampens ER stress-mediated ROS and minimizes ER stress phenotypes. B. dentium cell-free supernatant and γ-glutamylcysteine were taken up by human colonic T84 cells, increased glutathione levels, and reduced ROS generated by the ER-stressors thapsigargin and tunicamycin. Moreover, B. dentium supernatant and γ-glutamylcysteine were able to suppress NF-kB activation and IL-8 secretion. We found that B. dentium supernatant, γ-glutamylcysteine, and the positive control IL-10 attenuated the induction of UPR genes GRP78, CHOP, and sXBP1. To examine ER stress in vivo, we first examined mono-association of B. dentium in germ-free mice which increased MUC2 and IL-10 levels compared to germ-free controls. However, no changes were observed in ER stress-related genes, indicating that B. dentium can promote mucus secretion without inducing ER stress. In a TNBS-mediated ER stress model, we observed increased levels of UPR genes and pro-inflammatory cytokines in TNBS treated mice, which were reduced with addition of live B. dentium or γ-glutamylcysteine. We also observed increased colonic and serum levels of IL-10 in B. dentium- and γ-glutamylcysteine-treated mice compared to vehicle control. Immunostaining revealed retention of goblet cells and mucus secretion in both B. dentium- and γ-glutamylcysteine-treated animals. Collectively, these data demonstrate positive modulation of the UPR and MUC2 production by B. dentium- secreted compounds. Graphical abstract: uf0001